2016
DOI: 10.1073/pnas.1614048113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic updating of hippocampal object representations reflects new conceptual knowledge

Abstract: Concepts organize the relationship among individual stimuli or events by highlighting shared features. Often, new goals require updating conceptual knowledge to reflect relationships based on different goal-relevant features. Here, our aim is to determine how hippocampal (HPC) object representations are organized and updated to reflect changing conceptual knowledge. Participants learned two classification tasks in which successful learning required attention to different stimulus features, thus providing a mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
257
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 207 publications
(279 citation statements)
references
References 74 publications
(101 reference statements)
21
257
1
Order By: Relevance
“…In line with recent evidence, we identify representational changes indicative of a selective attention mechanism that tracks the predictive value of different stimulus dimensions during learning (Mack et al, 2016;Leong et al, 2017). The data suggest that attention to these goal-relevant cues enhances their representation in objectselective cortex quickly and persistently in a simple rule-based category learning task (Figure 3).…”
Section: Cc-by-nc-ndsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with recent evidence, we identify representational changes indicative of a selective attention mechanism that tracks the predictive value of different stimulus dimensions during learning (Mack et al, 2016;Leong et al, 2017). The data suggest that attention to these goal-relevant cues enhances their representation in objectselective cortex quickly and persistently in a simple rule-based category learning task (Figure 3).…”
Section: Cc-by-nc-ndsupporting
confidence: 89%
“…For example, MVPA has been used to test mechanistic theories of how attention modulates activation of predictive information being held in working memory (LewisPeacock and Postle, 2008;Lewis-Peacock et al, 2012) and how bottom-up attentional orienting to visual stimulus features (Leong et al, 2017) manifests in enhanced neural activation of these features in ventral temporal cortex. Applications of these attentional findings to category learning have shown that, as a result of learning, stimulus dimensions that are predictive of category membership become more prominent in activation patterns in ventral temporal cortex (Mack et al, 2013) and stored stimulus representations in the hippocampus come to reflect these attention-based changes in neural stimulus representations (Mack et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, hippocampal responses scale with the conceptual novelty of experiences [70, 71], and such signals may be critical to concept formation and updating [72, 73]. Further evidence for the role of the hippocampus and mPFC in formation of conceptual maps comes from a set of recent studies that use representational approaches to neuroimaging data analysis [20, 74, 75]. These studies have shown that the similarity of hippocampal [20, 75] and mPFC [74] activation patterns between individual concept exemplars scales with their distance in a learned conceptual space; exemplars of the same concept evoke more similar activation patterns in hippocampus and mPFC and are distinct from exemplars of different concepts (Fig.…”
Section: Integrated Maps Of Conceptual Spacementioning
confidence: 99%
“…Finally, new content is integrated with existing mental models via hippocampus—mPFC interactions [1719]. During integration, mPFC biases hippocampal encoding processes to emphasize representation of features common to multiple events [20, 21], resulting in cognitive maps that use overlapping neural codes to represent the relationships among discrete learning episodes [22, 23]. Here, we review recent evidence that hippocampus—mPFC memory integration mechanisms support the formation of cognitive maps across different domains of experience, including space, time, and concepts.…”
Section: Introductionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/178145 doi: bioRxiv preprint first posted online Aug. 23, 2017; counterbalanced across participants. This problem order was used for purposes 372 described in a prior analysis of this data (Mack et al, 2016 The classification problems consisted of learning trials (Figure 1a …”
mentioning
confidence: 99%